Deux ateliers de potiers en Dauphiné au bas Moyen Âge : les productions d’Aoste - Alban Horry (Archéologie Médiévale)
Excavations carried out in Aoste (Isère) on the “Normandoz” site, have made a significant contribution to our knowledge of the late-medieval pottery industry in the Dauphiné region. Analysis of part of two potters’ workshops is based upon the highly abundant pottery finds as well as evidence for structures and other finds related to the production site. The regional pottery repertory for the 14th and 15th centuries is substantially enhanced by the wares produced in Aoste. One of the most surprising discoveries is evidence for the manufacture of decorated stove-tiles during the 15th century. At this point, it is the southern-most example of production of objects traditionally associated with north-eastern Europe.